Political Economic Dilemma in Infrastructure Funding: The Impact of The Whoosh Project Debt on State Finances - Sherly Andari; Muhhamad Rizkie; Sri Yuningsih; Vidhini Nazhifa Rachmalimy; Firman Kurniawan; Dewi Yolanda Putri (Advances: Jurnal Ekonomi & Bisnis, 2026)
Purpose: This study analyzes the political economy and fiscal implications of the Jakarta–Bandung High-Speed Rail (Whoosh) project within the framework of China’s Belt and Road Initiative (BRI). Research Method: This study employs a qualitative explanatory case study approach using document analysis of government regulations, Ministry of Finance reports, KCIC publications, academic journals, and reports from international institutions. Results and Discussion: The findings show that the project’s financing structure increased fiscal exposure for Indonesian state-owned enterprises, particularly PT KAI, due to cost overruns and debt servicing pressures. The study also indicates that concerns about geopolitical dependency should be interpreted with caution, as domestic governance capacity, financing structures, and institutional risk management strongly influence the project outcomes. Implications: The study emphasizes the importance of transparent fiscal governance, stronger risk-sharing mechanisms, and comprehensive ex-ante fiscal evaluation for strategic infrastructure projects. Originality: This study integrates political economy and public financial management perspectives to explain the fiscal consequences of debt-financed infrastructure projects in developing countries.